Manajemen Pengetahuan dan Implementasinya dalam Organisasi dan Perorangan - Yugowati Praharsi (Jurnal Manajemen Maranatha, 2016)
Developing knowledge management has a great potential in Indonesia because of a huge population approximately 252 million people. The population becomes demography bonus and an important asset. In this study, we discussknowledge management concept in an organization and its implementation held in several regencies. Meanwhile, an implementation of personal knowledge management and supported technology also has been discussed. The results show that the implementation of knowledge management is necessary to map area, accelerate, and disseminate development in regency. Moreover, the implementationof personal knowledge management is essential to organize, categorize, and access data for a special purpose. The implementation of knowledge management in anorganization or personal boosts a business performance/result and its achievement.Keywords: Knowledge management, organization, personal, application program